Displaying Legitimacy: Monjas Coronadas Portraits and the New Spanish Family - (:unkn) unknown (My University, 2018)
Monjas coronadas (crowned nun) portraits are a uniquely New Spanish genre of painting that depicts a young woman on the eve of her profession as a cloistered nun. Situating the sitter as a Bride of Christ, she is adorned in a number of ornate and symbolic religious trappings, the most important of which is a large floral crown. The portraits are highly formulaic and feature New Spanish iconography that amplified these sitters’ elite status as nuns. Modern scholars, when discussing this genre of portraiture, focus on how the iconography of the images reflected the budding Creole culture. However, scholarship has yet to address the function of monjas coronadas portraits within the New Spanish home. Focusing on the iconography of the monjas coronadas portraits does not allow for a satisfactory explanation on the display of the paintings. Instead of focusing on the symbolic trappings pictured within the image, my argument analyzes the larger material culture of New Spain. My thesis will examine both how the portraits were displayed, and how the inscriptions found within the image helped to legitimize the elite status of the families that commissioned the paintings.
Keywords: Colonial portrait; Mexican portrait; Monjas coronadas; nun; portrait